The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3389/fcimb.2019.00378
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Candida Antigenic Factors: Structure-Driven Immunomodulation Properties of Synthetically Prepared Mannooligosaccharides in RAW264.7 Macrophages

Abstract: The incidence and prevalence of serious fungal infections is rising, especially in immunosuppressed individuals. Moreover, co-administration of antibiotics and immunosuppressants has driven the emergence of new multidrug-resistant pathogens. The significant increase of multidrug-resistant pathogens, together with their ability to form biofilms, is associated with morbidity and mortality. Research on novel synthetically prepared immunomodulators as potential antifungal immunotherapeutics is of serious interest.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 110 publications
(127 reference statements)
2
5
0
Order By: Relevance
“…By contrast, 500-1000 μg ml −1 M3-β-1,4 significantly inhibited the proliferation of macrophages (Figure 2a). In a previous study, Paulovicová demonstrated that treatment with synthetically prepared biotinylated mannooligosaccharides containing β-1,2-linked mannosyl units terminus could significantly increase the proliferation of RAW264.7, consistent with the findings of the present study (Paulovicova et al, 2019). Therefore, 125 and 250 μg ml −1 of MG, 1000 and 2000 μg ml −1 of M2-β-1,2, 250 and 500 μg ml −1 of M3-β-1,2, 250 and 500 μg ml −1 of M3-β-1,4 were selected for the following assays.…”
Section: Effects Of Mannosyl Compounds On the Viability Of Raw2647 Cellssupporting
confidence: 92%
“…By contrast, 500-1000 μg ml −1 M3-β-1,4 significantly inhibited the proliferation of macrophages (Figure 2a). In a previous study, Paulovicová demonstrated that treatment with synthetically prepared biotinylated mannooligosaccharides containing β-1,2-linked mannosyl units terminus could significantly increase the proliferation of RAW264.7, consistent with the findings of the present study (Paulovicova et al, 2019). Therefore, 125 and 250 μg ml −1 of MG, 1000 and 2000 μg ml −1 of M2-β-1,2, 250 and 500 μg ml −1 of M3-β-1,2, 250 and 500 μg ml −1 of M3-β-1,4 were selected for the following assays.…”
Section: Effects Of Mannosyl Compounds On the Viability Of Raw2647 Cellssupporting
confidence: 92%
“…Mannoproteins are adhesins (mannans with lectin-like properties , ) and promote Candida binding to endothelial and epithelial cells. Different Candida species have different glycan structures Fungal mannan antigenemia is also regarded as a diagnostic indicator of invasive Candida infections. , At present, we know little about the cell wall, the mannoproteins, mannans, and the glycome of C. auris .…”
mentioning
confidence: 52%
“…Hb and mannan both functioned as the adjuvants. As an oxygen carrier, Hb was a potential immunomodulatory protein without a significant adverse immune effect, which could regulate inflammation, cytokine secretion, and activation of macrophage in the plasma. , Mannan was a ligand of TLR-4 or TLR-2 and could be recognized via mannose receptor, dectin-2, and DC-SIGN, which induce Th1-type and Th2-type immune response. Hb and mannan could play the immunomodulatory activities in a synergistic manner. Consistently, physical administration of HM with EDIII was demonstrated to increase the immunogenicity of EDIII in the present study.…”
Section: Discussionmentioning
confidence: 99%